PNAEQ - 10 years of preanalytical EQAS in PORTUGAL - Cardoso, Ana (2018)
In the last 10 years, PNAEQ (Programa Nacional de Avaliação Externa da Qualidade) provided a specific program on preanalytical phase on its own responsibility. Since 2014, five more schemes were offered in this area: phlebotomy and POCT units, blood gas analysis, clinical chemistry and microbiology in collaboration with Labquality Oy, and haemostasis in collaboration with ECAT Foundation. The main objective of implementing a national and specific program on preanalytical phase is to evaluate the performance of laboratories nationwide on these matters and encourage them to improve their quality service. To reach this goal PNAEQ provided different types of assays and collected information from questionnaires and meetings with participants, in order to find tools to help on the evaluation of this important extra-analytical phase.